2011
DOI: 10.1002/joc.2307
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of downwelling longwave irradiance under all‐sky conditions

Abstract: This work is focused on the characterization and parameterisation of the downward atmospheric irradiance (LW) for clear and cloudy skies. LW is a component of the surface radiation budget that is present throughout the day. Unlike solar irradiance, LW is not measured routinely in extended networks, so it must be estimated indirectly. We evaluated five parameterisations for estimating LW under clear skies. After some consideration regarding the local fitting of the parameterisations, we analysed their different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
0
20
2
Order By: Relevance
“…Bilbao and De Miguel (2007) Crawford and Duchon (1999)'s cloudiness factor with the Brunt (1932) model was recommended for all sky conditions in these eleven sites in Florida, US. Alados et al (2012) demonstrated that the locally calibrated scheme of Brutsaert and origonal scheme of Berdalh and Martin showed best R ld estimations with root mean square deviation (RMSD) below $3.0% for clear sky conditions and the Crwaford and Duchon showed the best R ld estimations with RMSD below $6.0% for all sky conditions in Spain. Gubler et al (2012) demonstrated that the typical form of all sky R ld model presented in Eq.…”
Section: Downward Longwave Radiation For All Sky Conditionsmentioning
confidence: 97%
“…Bilbao and De Miguel (2007) Crawford and Duchon (1999)'s cloudiness factor with the Brunt (1932) model was recommended for all sky conditions in these eleven sites in Florida, US. Alados et al (2012) demonstrated that the locally calibrated scheme of Brutsaert and origonal scheme of Berdalh and Martin showed best R ld estimations with root mean square deviation (RMSD) below $3.0% for clear sky conditions and the Crwaford and Duchon showed the best R ld estimations with RMSD below $6.0% for all sky conditions in Spain. Gubler et al (2012) demonstrated that the typical form of all sky R ld model presented in Eq.…”
Section: Downward Longwave Radiation For All Sky Conditionsmentioning
confidence: 97%
“…7and 8, there are many other formulae for atmospheric emissivity calculations. The new methods are usually juxtaposed with oldest formulae, see, for example, Alados et al (2012), Duarte et al (2006), Flerchinger et al (2009), Iziomon et al (2003), Marthews et al (2012) and Santos et al (2011). The selected, used herein, formulae are summarised in Table 4.…”
Section: Longwave Atmospheric Radiationmentioning
confidence: 99%
“…Since formula (7) is commonly used in water quality modelling, it has been calibrated for many sites around the world; see, for example, Berdahl and Martin (1984), Berger et al (1984), FAO (1990), Heitor et al (1991, Iziomon et al (2003), Kjaersgaard et al (2007), Monteith (1961), Sellers (1965), and Swinbank (1963). In summary, according to different studies (Alados et al 2012;Elsasser 1942;Iziomon et al 2003;Jiménez et al 1987), the values for a 1 and a 2 coefficients range from 0.34 to 0.7 and from 0.023 to 0.110, respectively. Since the clear night-time sky is more emissive than the daytime, some authors, for example, Berdahl and Fromberg (1982) and Li et al (2017), suggest using different coefficients for the daytime and night-time, or propose a correction depending on the hour of the day (Alados-Arboledas and Jimenez 1988).…”
Section: Longwave Atmospheric Radiationmentioning
confidence: 99%
“…Dozens of parameterization formulas have been developed in which clear-sky effective emissivity is calculated as a function of the screen-level air temperature (T a ) and water vapor pressure (e), since about half the longwave radiation comes from the lowest 100 m of the atmosphere [1]. Details about the formulae for estimating emissivity are given by various authors [10][11][12]. Prata [13] found that the precipitable water content was much better to represent the effective emissivity of the atmosphere than the water vapor pressure.…”
Section: Introductionmentioning
confidence: 99%